2021
DOI: 10.3390/foods10061274
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Stable Isotopes and Fatty Acid Composition for Geographical Origin Discrimination of One Argan Oil Vintage

Abstract: Quality control and traceability of Argan oil requires precise chemical characterization considering different provenances. The fatty acid profile is an essential parameter that certifies the quality and purity of Argan oil. In addition, stable isotopes were recently shown to be accurate as an indicator for geographical origin. In this study, fatty acid composition by gas chromatography (GC) and stable isotope ratio by isotope ratio mass spectrometry (IRMS) were investigated for classifying Argan oil according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The nutritional benefits of unsaturated fatty acids are widely documented (36,37). Oleic acid (43-49 g/100 g) and linoleic acid (29-37 g/100 g) are the major unsaturated fatty acids found in argan oil (4,20,38). Linolenic acid, a very oxidizable molecule, is also present in very low concentrations usually <0.3 g/100 g (39).…”
Section: Fatty Acid Phytosterol Tocopherol and Volatile Compounds Com...mentioning
confidence: 99%
“…The nutritional benefits of unsaturated fatty acids are widely documented (36,37). Oleic acid (43-49 g/100 g) and linoleic acid (29-37 g/100 g) are the major unsaturated fatty acids found in argan oil (4,20,38). Linolenic acid, a very oxidizable molecule, is also present in very low concentrations usually <0.3 g/100 g (39).…”
Section: Fatty Acid Phytosterol Tocopherol and Volatile Compounds Com...mentioning
confidence: 99%
“…(2020) who have mentioned that the climate has affected the amount of triglycerides while the other parameters have not presented any difference between regions. In the same context Elgadi et al (2021a) have demonstrated that the fatty acids composition was influenced by the altitude and latitude, a high percentage of the linoleic acid was a marker of coastal argan oil, while the high content of palmitic acid was considered to be the marker of continental argan oil. On the other hand Elgadi et al (2021b) have shown that the tocopherols content of argan oil is strongly influenced by origin, the distance from the coast, and altitude.…”
Section: Discussionmentioning
confidence: 94%
“…This was done by selecting unauthenticated samples from the first LDA. The FA profile has been demonstrated to be a powerful indicator of geographic characteristics [2], and, specifically for…”
Section: Second Step I: Fa Composition For Geographical Authenticationmentioning
confidence: 99%
“…The use of stable isotopic values (C and N) in organisms can reveal the energy sources (organic sources) and their movement through the food web based on kinetic reactions (e.g., fractionation factor) [18,19]. It can also be adopted for geographical source tracing, as differences in sources and changes caused by specific processes can provide useful information for distinguishing groups of products based on geographical differences [2,19,20]. Thus, this approach has been used for tracing the raw-material sources of products, such as juice, wine, milk, honey, oil, and meat [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation